Towards a new approach of innovation in less developed regional business ecosystems - Fotios Katimertzopoulos; Charis Vlados (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: Most studies are undertaken using the differences in regional characteristics to either explain variations in the creation of innovation or interpret regional development forms based on innovative activities inside a region. However, many researchers suggest that businesses instead of regions are those that produce innovation, combining in their research the use of business data together with local characteristics The purpose of this article is to propose a new approach to innovation in less developed regional business ecosystems, focusing on the integration of business' strategy, technology and management dynamics. Design/methodology/approach: By performing a literature review, the purpose of this article is to investigate whether the policy on innovation is able to either aim at improving regional innovation conditions or focus more on the specific needs of SMEs in those regions. All these are envisaged and enhanced under the prism of a new approach to regional innovation systems: the Stra.Tec.Man (Strategy. Technology. Management) method. Findings: In summary, it seems that innovation may be concentrated on a practical field, with distinct targeting, but it must transplant the organism's intrinsic capability (material or intangible) in the particular circumstances of its external environment, within the specific regional dynamics. Its productivity, its innovativeness and, finally, its ability to survive and expand is always synthetically coordinated by the business (and its specific physiology), the industry (and its special dynamics) and the socio-economic environment (and its particular historical evolution). Research limitations/implications: Consequently, the present study was based on a literature review. The analyzes of the theoretical method of Stra.Tech.Man (initiated by the regionalism question in this study) are aimed at encouraging future research on innovation measurement in less-developed areas. Originality/value: The main objective of this study is to present the Stra. Tech. Man's multidimensional analytical specter, including the theoretical approach of innovation in order to map the factors that affect business ecosystem growth and development in less developed regions.
Keywords: O30; R11; 330; peripherality; innovation; regional and local underdevelopment; business dynamics and physiology; multi-level competitiveness; Stra.Tech.Man approach